Nitrogen induced ferromagnetism in Cobalt doped BaTiO3 - Chandrima Mitra (AIP Advances, 2012)
The electronic structure and magnetism of Cobalt doped BaTiO3 (BaTi1−xCoxO3) is investigated. Substitutional Nitrogen on an Oxygen site is found to play an important role in inducing net magnetic moments in the system. The presence of a Nitrogen atom as nearest neighbour to a Cobalt atom is crucial in producing spin splitting of both the Nitrogen and Cobalt states thereby introducing a net local magnetic moment. The introduction of Nitrogen is further found to enhance ferromagnetic interactions between Cobalt atoms.